CGIAR Initiative on Agroecology: Communications Plan - Staiger Rivas, Simone (2022)
This Communications Plan for the CGIAR Initiative Transformational Agroecology across Food, Land and Water Systems (AE-I) aims to provide guidance for people working with and for the Initiative as well as anyone who may need to speak or write about it.